Tracking bacterial effector protein delivery into host cells. Issue 3 (28th July 2021) - Cover, Timothy L.
Abstract: Bacterial Type IV secretion systems (T4SSs) are a functionally heterogeneous group of nanomachines that can deliver substrates into a wide range of target cells. The Helicobacter pylori Cag T4SS has an important role in the pathogenesis of gastric cancer. CagA, the only effector protein known to be secreted by the H. pylori Cag T4SS, enters human gastric cells and causes alterations in intracellular signaling that are linked to cancer pathogenesis. Understanding the molecular mechanisms by which CagA is delivered into gastric cells has been hindered by the lack of robust methods for monitoring this process. A publication in this issue of Molecular Microbiology describes a split luciferase assay for monitoring T4SS‐mediated translocation of CagA into host cells. The use of this translocation reporter allowed the quantification of CagA translocation in real‐time assays, thereby facilitating the analysis of the kinetics of CagA delivery. This system also allowed the tracking of several types of CagA fusion proteins and confirmed that protein unfolding is important for secretion by the Cag T4SS. This commentary discusses T4SS‐dependent delivery of H. pylori CagA into host cells and the use of the split luciferase system for monitoring bacterial protein secretion and delivery into target cells. Abstract : Bacteria can use several types of secretion systems to deliver effector proteins into host cells through contact‐dependent processes. This commentary discusses type IV secretion system‐dependent translocation of Helicobacter pylori CagA into gastric epithelial cells and the use of a split luciferase system for monitoring bacterial protein secretion and delivery into target cells.